Vouching the Digital Literacy in Instruction Viz-A-Viz Performance: Contextualized Enhancement Activities - Suico, Nikko; Gabuya Jr, Alden Q.; Bardoquillo, Charina; Briones, Zarmie Lis R.; Charcos, Angen May F.; Abaquita, Ma. Carla Y.; Abaquita, Rowena P.; Mancio, Arliezl D. (International Journal of Advanced Science Computing and Engineering, 2024)
The study determined the degree of digital literacy and the various ICT skills of Senior High School Students of Biasong National High School, Balamban, Cebu, for the academic year 2021-2022. Significantly, it aimed to identify the students' levels of digital access, specifically in terms of motivational access, material access, skills access, and usage access. The data was processed with the respondents' profiles to create contextualized enhancement activities that used the available materials and digital devices. Simple percentage, weighted mean, Pearson product-moment coefficient of correlation r, simple ranking, independent samples t-test, and one-way analysis of variance (ANOVA) were used with the descriptive-correlation methodology. Findings indicated that there is virtually no correlation between respondents' levels of digital access and their age, sex, and academic standing. Moreover, skills access and use access have low positive correlations with motivation access and overall digital access (r=0.398, p>0.01) and with each other (r=0.398, p>0.01). This implies that, although the correlation value is slightly higher than that of the other intercorrelations of factors, it still shows low correlation. However, there is a weakly positive correlation between Usage and Overall Digital Access Levels (r=0.516, p>0.01) as well as between Skills and Overall Digital Accesses (r=0.643, p>0.01). The Moderate association indicates that, despite the critical importance of digital device usage and ICT skills for developing digital literacy, respondents do not exhibit lower motivation or use digital devices less frequently.